Assessing Biometric Predictors of Gestational Age Among Pregnant Women in the Upper East Region of Ghana: The Quadratic Classifier Approach - Alhassan, Abukari (European Scientific Journal, ESJ, 2025)
Aims/Objectives: Gestational outcomes are influenced by a variety of maternal factors, including diabetes, yet not all pregnant women with gestational diabetes experience abnormal variations. It is, therefore, essential to examine additional predictors of gestational variations amongst women. Subject/Methods: Data were obtained from the Biostatistics Department of the War Memorial Hospital in Navrongo, Ghana. Records of 1085 mothers and their children were collected between January 2014 and January 2017, and analysed using the quadratic discriminant analysis to evaluate the impact of maternal and neonatal characteristics on gestational variation. Results: Maternal parity, age, and the weight of the newborn were the principal discriminating variables. Of these, parity was the most significant factor in distinguishing between deliveries below the Estimated Date of Confinement (EDC) within EDC, and above EDC. Conclusion: Parity was identified as the leading factor influencing gestational variation. The study recommends further research into the biochemical and physiological mechanisms linking parity to gestational outcomes.